Physiological indices of biological age in pregnant women of various age groups - K. V. Zubavina; S. B. Nazarov; A. I. Malyshkina; A. A. Akimova; A. B. Khuraseva (Акушерство, гинекология и репродукция, 2018)
The aims: to study the physiological indices, which characterize the biological age (BA) of the woman, in the process of physiological pregnancy and conduct a correlation analysis between these indices and the stage of pregnancy in different age groups. Materials and methods. Total of 122 pregnant women aged 20-34 years with different gestational age were selected for the study; all participants underwent a comprehensive functional examination. From the obtained results, the BA values were calculated using the in-depth «Kiev» scale as well as our own modification. Results. Upon an increase in the gestational age, there were changes in the BA-related indices in women of various age groups; these changes pertained to the vascular wall stiffness, respiratory functions, static balancing and the lens accommodation ability. Conclusion. The absence of changes in the BA, as calculated according to our modified test, during physiological pregnancy, suggests its applicability to women of young reproductive age. This calculation approach can be recommended for further studies in obstetrics and gynecology.